Immediate one-step lime precipitation process for the valorization of winery wastewater to agricultural purposes - Luz, Silvana (2021)
The winery wastewater (WW) of the Village of Vidigueira, in south of Portugal, presented an acid pH (4.26 ± 0.029), a high content of chemical oxygen demand (COD = 3236 ± 30.43 mg L-1), turbidity (160.0 ± 7.68 NTU), total P (155.5 ± 6.36 mg L-1) K (100.5 mg L-1), and low level of metals: Pb, Cd, Cu, Ni, Mn, Fe, Zn. The K and the total P content could make them attractive from an agricultural point of view. However, the high turbidity biochemical oxygen demand (BOD5 = 1266.7 ± 208.7 mg O2 L-1) fecal coliforms (45 ± 29.8 ufc/100 mL) and toxicological total phenols 13.239 ± 3.007 mg galic acid L-1 is the main limiting parameters. By using 5 g L-1 of lime solution, the best reactional conditions are achieved: pH = 12 with a minimum volume of the produced sludge's, 33.5 ± 4.92 mL L-1. These reactional conditions allow reaching high removal levels of BOD5, turbidity, total P, and total phenols: 77.9, 98.7%, 87.1%, and 99.9%, respectively. Simultaneously, the fecal coliforms and Enterococcus are 100% eliminated. The precipitate obtained is rich in calcium (2.7891 ± 0.4350 mg Ca kg-1) organic matter (10.05 ± 0.11%), P (895.0 ± 35.4 mg P2O5 kg-1), and K (990.0 ± 84.9 mg K2O kg-1). During carbonatation reactions, the pH (7.46) and electrical conductivity (EC) (1.805 dS m-1) decreased spontaneously while the Ca2+, K+, and F- kept high: 426.53 mg L-1, 240.53 mg L-1, 176.03 mg L-1, respectively.